What are the characteristics of disposable electronic cigarettes users in Switzerland? A quantitative study among 14-25 year olds - Luc Lebon; Karin Zürcher; Lorraine Chok; Diana Fernandes-Palhares; Jérémy Cros; Alexandre Dubuis; Cathy Berthouzoz; Yara Barrense-Dias (BMJ Publishing Group, 2024)
Introduction Disposable electronic cigarettes (DEC) appeared in Switzerland in 2020. The aim of this study is to determine the prevalence of DEC use among youth (14-25 year olds) living in French-speaking Switzerland and their characteristics.Methods Data were obtained from a web‐based survey conducted in August 2022. Participants were divided into four DEC user groups according to and were compared on sociodemographic data, substance use, family substance use and advertising viewing. Additional questions such as purchase methods and motivations were asked to the user groups.Results Among the 1362 participants, 41.2% had never used a DEC (NEVER), 14.4% once (ONCE), 15.1% several times but not in the last 30 days (PAST) and 29.2% several times in the last 30 days (CURRENT). At the multivariate level, compared with the NEVER group, participants in the CURRENT group were more likely to have used cigarettes and cannabis in the last 30 days, to report family electronic cigarettes use and to have seen online advertising for DEC. Among DEC users, compared with the ONCE group, those in the CURRENT group were less likely to be cisgender males, to have acquired their last DEC through peers or family and to use DEC out of curiosity.Conclusions Although most youth do not consume DEC regularly, these results raise concerns about growing exposure of young people to highly addictive products. They underline the importance of monitoring products availability, marketing and prevalence. They also confirm the necessity to inform the public, denormalise use and strengthen regulations.